Numerical studies on the effects of water presence in the coal matrix and coal shrinkage and swelling phenomena on CO2-enhanced coalbed methane recovery process. (1st January 2012) - Thararoop, Prob; Karpyn, Zuleima T.; Ertekin, Turgay
Conventional coalbed methane (CBM) models are developed using dual-porosity, single-permeability domain characteristics, which ignore the effects of water presence in the coal matrix. Neglecting these effects typically over-predicts gas production. Another phenomenon often disregarded in most CBM models is the coal shrinkage and swelling effects, which cause changes in coal permeability. This study illustrates how the water presence in the coal matrix and coal shrinkage and swelling phenomena affect the CO2 -enhanced CBM recovery process. An in-house two-phase, fully-implicit, compositional, dual-porosity, dual-permeability CBM simulator accounting for the effects of water presence in the coal matrix and coal shrinkage and swelling, is used in this analysis. Results demonstrate the water presence in the coal matrix caused an early CO2 breakthrough. A decrease in fracture permeability caused by the dominating effects of coal swelling delays the CO2 breakthrough. Ignoring these effects could provide significant errors of production predictions of enhanced CBM recovery process.